Level of technology acceptance on Assisted Reproductive Technology (ART) among ruminant farmers in Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
This study was conducted as a response to the slow pace movement of the uptake and utilization of assisted reproductive technologies towards ruminant animals. This study has been conducted among ruminant farmers in Kelantan, specifically in Bachok and Jeli district. Simple random sampling technique was employed and a total of 87 ruminant farmers were involved. From the analyzed data, the acceptance of assisted reproductive technologies is depicted at a moderate level. Hence, based on the result obtained, educational institutions together with government agencies is recommended to play their roles together as a body to educate local ruminant farmers to ensure the increment of beef and milk productions as well as reaching the self-sufficiency level.
Keywords: Assisted reproductive technology; ruminant farmers; meat; milk; production